Infective endocarditis following transcatheter mitral valve-in-valve replacement: a clinical case report - Jing-Wei Zhang; Si-ying Liao; Jie Li; Feng-Juan Yao (BMC Cardiovascular Disorders)
Abstract Background Transcatheter valve-in-valve replacement (TMViVR) is an alternative option for patients with bioprosthetic valve failure (BVF) who are at high surgical risk. Although infective endocarditis (IE) after transcatheter mitral valve-in-valve replacement is unusual, it is associated with significantly high mortality. Case presentation An 81-year-old male patient was admitted with intermittent thoracic tightness, chest pain persisting for 3 years, and shortness of breath with nausea for 1 week. Two months prior, he received transcatheter mitral valve-in-valve replacement for recurrent heart failure and severe prosthetic mitral regurgitation. He developed a fever in the early postoperative period after TMViVR, with Staphylococcus lugdunensis bacteremia detected. He was discharged from the hospital after the blood culture turned negative following antibiotic treatment. During this hospitalization, prosthetic valve endocarditis was confirmed, resulting in severe prosthetic mitral stenosis and severe pulmonary hypertension. Blood cultures identified Staphylococcus lugdunensis again. Despite anti-infective therapy, the patient succumbed to complications from his complex medical history and comorbidities. Conclusions While transcatheter valve implantation provides an alternative option for dealing with valvular disease, prosthetic valve endocarditis (PVE) as an unusual but catastrophic complication with poor prognosis should be taken seriously. Early detection through echocardiography, especially in high-risk patients presenting with suspicious symptoms, is crucial for timely intervention. Additionally, an appropriate perioperative antibiotic regimen is essential to prevent infection and improve prognosis.